1989
DOI: 10.1002/tea.3660260104
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes toward science and sciencerelated careers: A program designed to promote a stimulating gender‐free learning environment

Abstract: A project designed to foster the full and fair participation of girls in high‐school science classes addressed obstacles, both perceived and actual, to equal participation. In order to modify existing classroom techniques and environments, a Teacher Intervention Program was designed. By means of a workshop and periodic personal communications, teachers were sensitized to the importance of a stimulating, gender‐free learning environment. In addition, they were presented with a variety of methods and materials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 11 publications
2
55
2
Order By: Relevance
“…Another finding of the study supports the commonly held belief that students' attitudes toward science tend to become more negative as students grow older-i.e., pass on to higher grades (Doran & Sellers, 1978;Koballa, 1988a;Mason & Kahle, 1989;Oliver & Simpson, 1988Rennie & Punch, 1991;Stead, 1985). When the five independent variables were taken into consideration, ATS was found to be a significant predictor of behavioral intention for laboratory activities.…”
Section: Discussionmentioning
confidence: 92%
“…Another finding of the study supports the commonly held belief that students' attitudes toward science tend to become more negative as students grow older-i.e., pass on to higher grades (Doran & Sellers, 1978;Koballa, 1988a;Mason & Kahle, 1989;Oliver & Simpson, 1988Rennie & Punch, 1991;Stead, 1985). When the five independent variables were taken into consideration, ATS was found to be a significant predictor of behavioral intention for laboratory activities.…”
Section: Discussionmentioning
confidence: 92%
“…The importance of environmental influences outside of school has been the focus of numerous studies (Farenga, 1995;Kahle et al, 1993;Majoribanks, 1991;Mason & Kahle, 1989;Walberg, 1991). The aggregated effect that experience provides can form the foundation to subsequent learning.…”
Section: Informal Science Experiencementioning
confidence: 99%
“…It is probable that there was a degree of pre-test contamination (Mason and Kahle, 1988); some teachers reported that during post-test administration, students complained that they had 'already answered the questions'. We do not draw on these data in this paper.…”
Section: Student and Parental Questionnaires: Design Challenge And Amentioning
confidence: 99%